Determination of Foveal Avascular Zone in Diabetic Retinopathy Digital Fundus Images - Lila Izhar, Iznita; Ahmad Fadzil, M Hani; Nugroho, Hanung Adi (Elsevier BV, 2010)
Monitoring FAZ area enlargement enables physicians to monitor progression of the DR. At present, it is difficult to discern the FAZ area and to measure its enlargement in an objective manner using digital fundus images. A semi-automated approach for determination of FAZ using color images has been developed. Here, a binary map of retinal blood vessels is computer generated from the digital fundus image to determine vessel ends and pathologies surrounding FAZ for area analysis. The proposed method is found to achieve accuracies from 66.67% to 98.69% compared to accuracies of 18.13% - 95 .07% obtained by manual segmentation of FAZ regions from digital fundus images.